The role of branching in the ultrafast dynamics and two-photon absorption of two pyrimidine push–pull molecules - Katsidas, Alexandros; Fecková, Michaela; Bureš, Filip; Achelle, Sylvain; Fakis, Mihalis (Royal Society of Chemistry, 2025)
The dynamics and two-photon absorption (2PA) properties of two pyrimidine chromophores are studied using femtosecond time-resolved fluorescence and two-photon excited fluorescence techniques. The pyrimidine is used as an electron withdrawing group and is substituted at the C2 position with a phenylacridan fragment, while diphenylaministyryl donor moieties are appended at positions C4/6 to afford the pseudo-dipolar and pseudo-quadrupolar molecules 1 and 2, respectively. Chromophore 2 shows more efficient fluorescence emission, while 1 exhibits larger Stokes shifts. Their decay pathways are discussed through an emission from a Franck–Condon charge transfer (FC-CT) and a relaxed charge transfer (R-CT) state. Ultrafast dynamics in tetrahydrofuran show population of the R-CT state for 1 that is faster than solvation, while for 2, due to its pseudo-quadrupolar nature, R-CT population is slower and occurs from the solvated FC-CT state. Finally, molecule 2 shows better 2PA properties with cross sections reaching 560 GM at 820 nm.